940 In-situ simulation in the paediatric emergency department: Improving patient safety, encouraging teamwork and delivering education. (17th August 2022) - Riddick, Laura; Jones, Elizabeth; Hall, Emma
Abstract : Aims: We want to improve the quality and safety of patient care within the paediatric emergency department (PED). We want to be able to deliver education, encourage teamwork and communication, and identify and act upon clinical risk seen in the PED. We look to use in-situ simulation to address these issues. Methods: By introducing monthly in-situ simulation we run a 15-minute scenario with a 15 minute debrief of how it went. We involve many different allied health professionals from ED, paediatrics and other specialities. We acquire feedback with learning points and use this to improve future simulations. Through in-situ simulation training: 1. We are able to provide education and training to junior staff, which can be disseminated to the rest of the team 2. We are able to involve multi-disciplinary teamwork as well as involve different specialities in the training process, promoting interprofessional learning 3. We are able to implement and 'test' new guidelines and policies 4. We are able to witness any human or environmental factors, such as access to medications in the drug cupboard in resus, and act upon this. 5. We can provide an environment to test out new devices such as transport vapotherm 6. Enable to act upon clinical risks and incidences 7. Identify common learning mistakes or beliefs and correct this through simulation summaries that are shared amongst the team. Results: Examples of simulations covered and their outcomes 1. Asthma – was able to test and introduce the new flow chart and witness accessibility issues in making up magnesium IV. 2. Bronchiolitis – we were able to assess how to use the transport vapotherm and identified difficulties in setting it up leading to more training on it 3. Congenital Cardiac disease – we were able to introduce a new version of Prostin and educate the nursing team on how to make it up and administer 4. Major trauma – we identified we had no major haemorrhage protocol in paediatrics so this has been designed. Feedback: Subjectively participants have said their knowledge of the conditions increased by 40% and they feel more confident managing these conditions. Participants were able to give 3 learning points from each session with roughly 60 participants per year being involved. Going forward Based on feedback we have received we have designed further in-situ simulations based on recent critical events including preterm delivery, head injury with coagulopathy and anaphylaxis. Conclusion: In-situ simulation has been shown to improve patient care in the paediatric emergency department through a multi-faceted approach leading to better teamwork, delivery of education and improved patient safety.